Organisational and social work-environment experiences after care manager implementation: a repeated cross-sectional study in Swedish primary care - Pia Augustsson; Eva-Lisa Petersson; Cecilia Björkelund; Sven Persson Kylén; Carl Wikberg (Scandinavian Journal of Primary Health Care)
Introduction Primary care centers (PCCs) are the foundation of healthcare, requiring a supportive work environment for quality care and personnel well-being. To address rising common mental disorders (depression, anxiety, stress-related disorders) care managers were introduced in Region Västra Götaland in 2015 and are now established in 175 PCCs, supported by clinical and economic benefits. This study explores changes in the organisational and social work environment experienced by PCC personnel five years post-implementation of care managers at two points: 2016/17 and 2021/22.Materials and methods This repeated cross-sectional study was conducted as an open cohort at 36 strategically selected PCCs in 2016/17 and 2021/22. Although the personnel varied, consistent instruments were used. Descriptive statistics and cross-tabulations examined differences in the organizational and social work environment at the two periods.Trial registration NCT02378272, 2015-02-02. Retrospectively registered.Results Familiarity with the care manager function increased from 72% in 2016/17 to 79% in 2021/22. Motivation to collaborate increased by 80%, reflecting a 62% higher willingness compared to 2016/17. Personnel’s knowledge and motivation were significantly associated with perceived improvements in the work environment. These improvements were consistent across gender, age, PCC size, and geographic location. Personnel at smaller PCCs reporting slightly greater improvements, with some age-related variation.Conclusions Having a care manager on site may have limited direct impact on individual work or perceptions of the work environment. However, increased knowledge of the function appears to strengthen collaboration collegial support within the PCC, indicating positive changes in the social and organisational work environment.